Analisis Makna Label Tasya Farasya Approved - Fitri Nuraeni; Weni A. Arindawati; Tri Widiya Budhiharti (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
This study aims to explore the meaning contained in the Tasya Farasya Approved label through Roland Barthes' semiotic approach. Data was collected through direct observation of the content published by Tasya Farasya on social media platforms and a literature review of related studies. This label does not only function as a visual complement but is part of the visual communication strategy used by Tasya Farasya, a well-known beauty influencer in Indonesia, to build a credible, authoritative, and convincing image for the products she endorses. This research is qualitative in nature and uses a semiotic analysis approach. Based on the results of denotative analysis, the label consists of visual elements such as the text "Tasya Farasya" and the word "Approved," an illustration of a face, a circular shape, a combination of purple and pastel yellow colors, and a star symbol. At the connotative level, these elements reflect symbolic meanings related to personal authority, exclusive value, and the representation of feminist beauty. Meanwhile, at the mythical level, these meanings undergo naturalization and form a collective belief that products bearing this label have guaranteed quality. This research contributes significantly to understanding how visual symbols in digital communication, especially in the beauty industry, can shape public perception and reinforce the digital consumption culture in Indonesia.